DISCUSSION ASPECTS OF INFORMATION AND COMMUNICATION TECHNOLOGIES COMPETENCIES: SNTERNATIONAL APPROACHES AND UKRAINIAN PROSPCTS - Gurzhiy А.М.; Ovcharuk О.В. (Journal of Information Technologies in Education (ITE), 2013)
The article deals with the discussion questions analysis on the information and communication competence in the international and domestic educational environment. The approaches to the information and communication competence notion are revealed. The terms in ICT area are described with the aim to understand the place and role of the information and communication competence. The discussion context in terms of IT-competence is described. The analysis of EU strategic documents and other international education policy papers is done.